Update of Red Sea (Lessepsian) fish species in the Mediterranean Sea since the 2nd CIESM Atlas of Exotic Fish - GOLANI, DANIEL (Mediterranean Marine Science, 2025)
The article presents data about Red Sea fishes in the Mediterranean (Lessepsian migrants) collected since the publication of the 2nd edition of the Atlas of Exotic Fishes in the Mediterranean, which included material until 2020. In the past five years, a total of 18 Lessepsian fish species were recorded, representing 12 families. Five of these have established populations in the Mediterranean and ten have significantly expanded their distribution (by at least 400 km) in the Mediterranean. Three of the species reported as Lessepsian migrants were based on misidentifications.